PEMERIKSAAN TEMPAT KEJADIAN PERKARA KECELAKAAN LALU LINTAS DAN PERKARA KEJAHATAN - Candra, Addy (MAJALAH KEADILAN, 2021)
Inspection of the crime scene in general, also presented the tactics of examining several types of crimes, which often arise and are often handled by patrol officers. Types of examination of the crime scene or cases include, among others, examination of the scene of a traffic accident, examination of the place of theft in Articles 362 and 363 of the Criminal Code, examination of the scene of a murder case as regulated in Article 338 of the Criminal Code, examination of the place of occurrence of cases of persecution regulated in Article 351 of the Criminal Code. The place of the case is the place where a criminal act occurred, or the consequences thereof and/or other places where evidence or victims related to the crime exist. Place of Genesis Cases have a narrow meaning and a broad meaning. In a narrow sense, namely the Place of Case where a crime occurs. Whereas in a broad sense, the crime occurred and other places where evidence or victims related to the crime. For patrol officers, it is necessary to pay attention to, namely in places that are vulnerable and quiet where a criminal act is being committed by the suspect, in a place like this the patrol must visit and carry out the activities that are being carried out by the patrol officer.